Indonesian Fiqh in Higher Education: A Pathway to Moderate and Inclusive Islamic Values - Hasbiyallah Hasbiyallah; Busra Nur Duran; Saca Suhendi (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2024)
This study aims to examine the incorporation of Indonesian fiqh into the Islamic higher education curriculum and its impact on fostering moderate attitudes among students. The research highlights the importance of ijtihad (independent reasoning) in adapting Islamic law to the contemporary needs of Indonesian society, emphasizing values such as gender equality, interfaith harmony, and democratic principles. The study employs a qualitative method, analyzing the curriculum content and its practical applications in three prominent Islamic universities: UIN Syarif Hidayatullah Jakarta, UIN Walisongo Semarang, and UIN Sunan Gunung Djati Bandung. Results indicate that the Indonesian fiqh curriculum is expected to significantly contributes to shaping students' moderate attitudes by promoting respect for human dignity, inclusivity, and adaptability. The curriculum encourages students to integrate religious, social, cultural, and state morals, fostering a balanced and comprehensive understanding of Islamic teachings. Themes such as women's emancipation and interreligious relationships are emphasized, highlighting the relevance of Islamic principles in modern contexts. Practical applications through social activities, community service, and leadership opportunities further reinforce these values, enabling students to act as agents of change. In conclusion, the Indonesian fiqh curriculum plays a crucial role in nurturing well-rounded, moderate, and compassionate individuals. By aligning with national needs and promoting inclusive values, it ensures that students are equipped to navigate and positively contribute to a diverse and dynamic society. This holistic approach fosters peace, harmony, and national development, making the Indonesian fiqh curriculum an essential component of Islamic higher education.